Ankle injuries in sports: anatomical considerations and clinical implications - Syarifah Aisyah Sah,; Elvy Suhana Mohd Ramli,; Srijit Dass,; Norzana Abd. Ghafar, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Ankle injuries are commonly seen in various sports. The main aim of the present review was to highlight the normal anatomy of the ankle, mechanism of injuries related to sports, congenital abnormalities or anatomical variations related to ankle injury and discuss its effective management. A review of literature was done to determine the ankle injuries which occur as a result of various sports related activities. We documented all sports which involved injury to the ankle joint. The anatomy of various structures in the sole of foot and their involvement in injuries were discussed at length. The anatomical knowledge of ankle injury may be beneficial for future diagnosis and treatment purpose.